Catchment response to climate and land use changes in the Upper Blue Nile sub-basins, Ethiopia - Woldesenbet, Tekalegn Ayele; Elagib, Nadir Ahmed; Ribbe, Lars; Heinrich, Jürgen (The Science of the total environment, 2018)
The impacts of climate and land development on streamflow and water balance components were analyzed in the Tana and Beles watersheds by using the Soil and Water Assessment Tool (SWAT). Streamflow response to simultaneous future land-use and land-cover (fLULC) and climate change (fCC) scenarios on the seasonal scale varied among the key water abstraction locations. The General Circulation Models (GCMs) average simulation of short-term climate indicated wetter and warmer climatic condition compared to that in the baseline period (1971/1980–2013). The near–future climate scenario would intensify extreme flow by increasing rainy season flow and reducing dry period flow. However, conversion of cultivation land on steep slope into forest might mitigate these extreme flows. At the outlet of Tana watershed, streamflow response would be amplified under concurrent scenarios of fLULC and fCC; but the streamflow would have an augmenting response at the outlet of the Beles watershed. Compared to response due to fCC alone, the streamflow and surface runoff components under combined fLULC and fCC scenarios would be alleviated in sub-catchments subject to conversion of cultivation in steep slope into forest land. The present results have significances for water resource management and land use planning in the Tana and Beles watersheds, and for other regions encountering identical pressures from climate change and LULC dynamics. In view of ongoing land use and climate dynamics, environmental policies must be carried out to cope with the potential changes of hydrologic regime. Moreover, catchment management should be adapted to changing hydrological regimes at different water abstraction points. [Display omitted] •Climate in the study area is projected to be warmer and wetter in near-future.•SWAT was used to assess the combined effects of climate and LULC change scenario.•Climate scenario would intensify extreme flow in both sub-basins.•LULC scenario might mitigate these extreme flows due to climate change.•GCMs simulated rainfall underestimated historical rainfall during rainy season.